Electrophysiological Evidence on Mirror Therapy for Promoting Perceptuo-Motor Processes in Stroke Patients - Li Ding; Dan Wang; Chengcheng Wu; Xu Wang; Jinyang Zhuang; Xiaoli Guo; Jie Jia (IEEE, 2024)
Mirror therapy is proposed to enhance post-stroke awareness of the affected limb and mental ability, but convincing evidence on the perceptuo-motor processes is insufficient. In this study, we aimed to investigate the longitudinal effect of mirror therapy on limb perception and early motor processes in stroke patients using the hand mental rotation (HMR) task with both behavioral and electrophysiological evidence. Fifty stroke patients were randomly assigned to a mirror therapy group (MG, N =25) or a conventional treatment group (CG, N =25). Before and after 4-week intervention, the HMR task was performed, and its behavioral performance and EEG characteristics were measured and correlated with clinical outcomes. Behavioral analysis showed that enhanced accuracy of the HMR task, correlating with greater improvement in upper extremity motor function, was only observed in the MG. The ERD/ERS and brain network analysis revealed significant group differences in brain activation and local network metrics in the ipsilesional hemisphere during the preparation and execution of mental rotation while processing the affected hand stimuli. Specifically, the MG showed enhanced ipsilesional parietal ERD in the $α $ (8-13 Hz) and $β 1$ (13-20 Hz) bands, along with increased ipsilesional centroparietal nodal strength and betweenness centrality, which were cross-correlated. The results indicate the potential of long-term mirror therapy for promoting perceptuo-motor processes, facilitating visuospatial perception, and improving motor preparation and mental ability of the affected limb, thereby contributing to post-stroke recovery.